Kombinasi Nira Kelapa(Arenga pinnata (Wurmb) Merrill) dan Sitrat dalam Pengawetan Semen Domba - Jalius, Jalius (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The  purpose  of  this  study  to  identify  the  combination  of  the Arenga  pinnata  (AP)    toddy with Citrate  diluent in sheep semen preservation at room temperature. This research conducted laboratory of Reproductive  Physiology,  Husbandry  Faculty,    University  of  Jambi.  In  this  study  using  a  random factorial design in a series of time with 5 treatment combinations and citric coconut palm is P0 = control, P1 = + 2.5% AP + citrate, P2 = 5% AP + citrate, P3 = 7.5%AP + citrate and P2 = 10%AP + citrate, with a  time of observation 0, 2, 4,  6 and 8 hours. Parameters are observed and viabelitas motility.The results of this study showed that administration of the Arenga pinnata toddy 7.5% + citrate diluent can sustain  sheep  spermatozoa motility  (P <0.01). However  viabelitas  concentration was maintained until 10% Arenga  pinnata  toddy. The  interaction  between  treatment  and  the  time  is  10% Arenga  pinnata toddy is good for storage of sheep semen within 2 hours. Conclusion using Arenga pinnata toddy   from 7.5  to  10%  can  maintain  spermatozoa  motility  and  viability  of  the  sheep  that  are  stored  at  room temperature.